1117 FAMILY SCREENING IN DILATED CARDIOMYOPATHY: CLINICAL CHARACTERIZATION AND FOLLOW UP OF RELATIVES. (15th December 2022) - Del Mestre, Eva; Loco Detto Gava, Carola Pio; Paldino, Alessia; Dal Ferro, Matteo; Gigli, Marta; Merlo, Marco; Sinagra, Gianfranco
Abstract: Background: Familial patterns of inheritance and genetic mutations have been identified as pathogenic in nearly 40-50% of previously defined "idiopathic" Dilated Cardiomyopathy (DCM). Genetic testing in the proband allows cascade genetic screening in relatives, in order to promote an early diagnosis even in a pre-clinical stage of the disease, as recommended by international guidelines. This study aims to describe the clinical characteristics of screened relatives of Dilated Cardiomyopathy (DCM) patients, at baseline and during follow-up. Methods: Screened relatives of patients affected by DCM were enrolled retrospectively and followed from January 2000 to August 2021. At baseline, the family screening included a clinical evaluation, ECG and echocardiogram. If likely pathogenetic (LP) or pathogenetic (P) variant was identified in the proband Genetic testing was offered and performed on relatives according to available consensus documents from the age of 10-12 years. The onset of disease was defined as left ventricular (LV) dilation and/or LV systolic dysfunction. The following information was obtained during the follow-up: all-cause death, cardiovascular death, sudden cardiac death (SCD), hospitalization for heart failure (HF), heart transplantation, ventricular assist device (VAD) implantation, ICD or CRT-D implantation and major ventricular arrhythmias (MVA). Results: We enrolled 203 relatives from 32 families with DCM. The median follow-up was 94 months. At baseline, symptomatic relatives for dyspnea (NYHA II-III class) were 29 (14%), versus 174 (86%) of asymptomatic (NYHA I). All these subjects showed initial signs of DCM and experienced more frequently adverse outcomes, such as hospitalization for HF (p<0, 001) and MVA (p<0, 001) during follow-up. Among asymptomatic relatives, patients with initial signs of disease were 46 (26%), 20 (43%) with LV dilation and dysfunction, 18 (39%) with LV dysfunction and 7 (15%) with LV dilatation. During follow-up, 5 of them (11%) died and 2 (4%) experienced SCD (one carrier of FLNC variant). Globally, affected relatives at baseline carried a LP/P variant in more than half of the cases (57%), the remaining part being relative of proband with no or negative genetic testing. Non-affected relatives were 128 (74%) at baseline. 15 relatives (12%) developed initial signs of DCM (5 with LV dilation, 5 with LV dysfunction, 5 with LV dilation and dysfunction) during follow-up. Of those, 13 patients (87%) carried a LP/P variant. The genes mostly involved were TTN (9 cases, 69%), followed by DSP and FLNC. Conclusions: Familial screening allows an early diagnosis of DCM-affected patients. Asymptomatic relatives at the baseline showed a better outcome compared with symptomatic ones. However, SCD events were only detected in the asymptomatic group. Moreover, subjects who develop the disease during follow-up were carriers of a LP/P variant. Seriate follow-up is mandatory in relatives independently by symptoms at the baseline: genetic testing supports a focused clinical screening of high-risk relatives.